Avaliação preliminar da viabilidade de produção in vitro de um isolado brasileiro de baculovírus Spodoptera frugiperda MNPV - Almeida, Andréa Farias de (2005)
In vivo production of viral biopesticides is the major source of viral insecticides currently in the marketplace. However, this system presents limitations during production scale-up. For the Spodoptera frugiperda nucleopolyhedrovirus (SfMNPV), the insect used for replication has cannibalistic characteristics, thus production is even more difficult. Insect cells are commonly used for in vitro baculovirus production. Most of these cell lines are derived from Lepidoptera species. The Sf21 cell line is derived from Spodoptera frugiperda caterpillar ovarian tissue, and its clonal isolate Sf9 has been used for biopesticide production due to its ease of growth in suspension cultures. In this work, the in vitro production capabilities of a Brazilian SfMNPV isolate obtained from cornfields was evaluated. Comparison of polyhedra production was carried out using both Sf21 and Sf9 cells, based on volumetric and specific yields. Both cell lines were cultivated in Hyclone medium supplemented with different fetal bovine serum concentrations (2,5 and 5%). The best results were obtained using Sf9 cells supplemented with 5% serum. These results were further confirmed quantitively through kinetic parameter estimation for both cells lines and different serum concentrations. After seven successive passages, this system still presented high specific polyhedra production